2011
DOI: 10.1038/onc.2011.461
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin/LEF1 transactivates the microRNA-371-373 cluster that modulates the Wnt/β-catenin-signaling pathway

Abstract: The microRNA-371-373 (miR-371-373) cluster is specifically expressed in human embryonic stem cells (ESCs) and is thought to be involved in stem cell maintenance. Recently, microRNAs (miRNAs) of this cluster were shown to be frequently upregulated in several human tumors. However, the regulatory mechanism for the involvement of the miR-371-373 cluster in human ESCs or cancer cells remains unclear. In this study, we explored the relationship between this miRNA cluster and the Wnt/β-catenin-signaling pathway, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 39 publications
3
105
2
2
Order By: Relevance
“…26 Furthermore, miR-373 and miR-372 can engage in an oncogenic feedback loop with members of the Wnt/β-catenin pathway. 20 However, although these reports imply that miR-371-373 possess oncogenic activities, other studies reveal that they can display tumorsuppressive features, 22,27,44,49 as observed also here. This dichotomous behavior of miR-373 and other chromosome 19 miRs is not unusual.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…26 Furthermore, miR-373 and miR-372 can engage in an oncogenic feedback loop with members of the Wnt/β-catenin pathway. 20 However, although these reports imply that miR-371-373 possess oncogenic activities, other studies reveal that they can display tumorsuppressive features, 22,27,44,49 as observed also here. This dichotomous behavior of miR-373 and other chromosome 19 miRs is not unusual.…”
Section: Discussionsupporting
confidence: 57%
“…19 The miR 371-373 cluster, expressed in human embryonic stem cells, is involved in stem cell pluripotency. 20 We subsequently chose to focus on one representative of each cluster: miR-512-5p (miR-512), belonging to the C19MC cluster, and miR-373. qRT-PCR analysis confirmed that miR-512 and miR-373, both nearly undetectable in A549 cells, were highly induced by 5′ aza+TSA (Figures 2c and d).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that other oncogenic miRNAs such as miR-372, 373 and 29a can directly target DKK1 promoting oncogenesis and chemoresistance in other cancers. 45,46 Of note, we also show that melphalan in the presence of miR-152 mimic sensitized MM cells to a more pronounced apoptotic cell death. Melphalan has been demonstrated to induce apoptosis either alone or in combination with other drugs through various canonical mechanisms.…”
Section: Discussionmentioning
confidence: 73%
“…The AXIN/GSK3b/APC complex normally promotes the proteolytic degradation of b-catenin, and so if this 'b-catenin destruction complex' is inhibited, b-catenin can accumulate, stabilize and enter the nucleus and then interact with the TCF/LEF family transcription factors, which promote specific gene expression. Recent studies linking WNT signalling and pluripotency have shown that the human NANOG gene is regulated through a TCF/LEF element within an enhancer (Kim et al, 2011a), while a pluripotency-associated micro-RNA (miRNA) cluster (miR-371-373) (Wang et al, 2008;Judson et al, 2009) was found to be positively regulated by WNT/b-catenin signalling activity in several human cancer cell lines (Zhou et al, 2011). Lithium chloride (LiCl)-mediated inhibition of GSK3 and b-catenin ubiquitination (Klein and Melton, 1996) stimulated WNT/bcatenin activity and subsequently stimulated the expression of the miRNA cluster through direct binding of b-catenin/ LEF1 to the miRNA promoter.…”
Section: Wnt Pathway Modulation and Pluripotencymentioning
confidence: 99%